2019
DOI: 10.1177/0958928719868443
|View full text |Cite
|
Sign up to set email alerts
|

The institutional logic of giving migrants access to social benefits and services

Abstract: The article analyses how the programmatic structure of welfare schemes in Denmark, the Netherlands and Germany shape public perceptions of and preferences for migrants’ entitlement to social benefits and services. First, the article finds that despite high complexity and the presence of some severe misconceptions, the entitlement criteria of migrants within existing social benefits and services do shape public perceptions of reality. Second, the article finds that these institutional shaped perceptions of real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…The adoption of a ‘solidarity’ perspective arguably enables them to better account for the diversity in immigrants’ access to social rights as opposed to ‘exclusion’, which suggests a dichotomy. However, it must be noted that apart from very few instances, which indicated that the concept ‘welfare chauvinism’ is ‘loaded’, ‘ambiguous’ or invokes ‘associations’ among readers (Koning, 2013: 3; Albrekt Larsen, 2020: 49; Carmel and Sojka, 2021: 646), these authors do not satisfactorily explain their movement away from this concept. Given that these studies refer to the same phenomenon as the studies which use the term ‘welfare chauvinism’, stem from the same definitional roots and use similar measures, we argue that their use of different concepts should be explicitly elaborated upon.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The adoption of a ‘solidarity’ perspective arguably enables them to better account for the diversity in immigrants’ access to social rights as opposed to ‘exclusion’, which suggests a dichotomy. However, it must be noted that apart from very few instances, which indicated that the concept ‘welfare chauvinism’ is ‘loaded’, ‘ambiguous’ or invokes ‘associations’ among readers (Koning, 2013: 3; Albrekt Larsen, 2020: 49; Carmel and Sojka, 2021: 646), these authors do not satisfactorily explain their movement away from this concept. Given that these studies refer to the same phenomenon as the studies which use the term ‘welfare chauvinism’, stem from the same definitional roots and use similar measures, we argue that their use of different concepts should be explicitly elaborated upon.…”
Section: Discussionmentioning
confidence: 96%
“…While some scholars propose to abandon the term altogether and adopt a different theoretical take (Carmel and Sojka, 2021), others see benefit in studying the phenomenon as defined by Andersen and Bjørklund (1990), but opt for using terms other than ‘welfare chauvinism’. For example, Degen et al (2019) prefer ‘welfare state restrictiveness’, which they associate with ‘whether and under which conditions immigrants should be granted access to social benefits’ (p. 2), and measure with the same ESS item used by many scholars to measure welfare chauvinism, while Albrekt Larsen (2020) uses ‘welfare nationalism’ as a synonym for welfare chauvinism to mitigate for the latter’s perceived normativity, and measure it with an ESS-like item. Other scholars add qualifying adjectives to ‘solidarity’.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are few publications that have provided a systematic analysis of the determinants of attitudes to free movement in the EU (Blinder & Markaki, 2019b;Larsen, 2020;Lutz, 2020;Meltzer et al, 2020;Vasilopoulou & Talving, 2018), and none of them have analysed the role of welfare institutions. The broader research literature on links between welfare states and attitudes to immigration and access to social rights for migrants (e.g., Sainsbury, 2012) is also relatively limited.…”
Section: Theory and Previous Researchmentioning
confidence: 99%